Parental Contribution to Early Childhood Development in the Digital Era - Miftahul Huda; Elok Halimatus Sa’diyah (Feelings: Journal of Counseling and Psychology, 2024)
The role of parents in early childhood development is a crucial factor in the process of child growth and development. In the context of limited face-to-face learning, this research will discuss the extent of parents' responsibilities in accompanying children to learn, as well as the urgency of parents' role in children's development from a developmental psychology perspective. The research method used is qualitative with analysis referring to trusted literature such as journals, books and other references. The research results show that parental responsibility and the strategies implemented by them are the main keys in dealing with psychological aspects of child development. Parental involvement during the learning period has a significant impact on child development. The factors that influence it involve internal and external elements in the child's environment.